2013
DOI: 10.5267/j.msl.2012.10.037
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social and environmental disclosure in developing countries: Evidence from Iran

Abstract: This research aims to investigate the extent of social and environmental disclosure (SED) in corporate annual reports. Specifically, This is an exploratory study designed to examine the relationship between corporate social and environmental disclosure (CSED) and corporate attributes and firm-specific factors in a developing country, Iran. In order to do this, we use content analysis approach with sentence count for the level of disclosure measurement by looking into the annual reports of the 66 listed compani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…Content analysis has been extensively used in examining SED practices (Kamal and Deegan, 2013; Novelini and Fregonesi, 2013; Pesci and Costa, 2014; Rahma and Anis, 2013; Talebnia et al , 2013; Van de Burgwal and Vieira, 2014). Content analysis refers to the process of making inferences based on objective coding of information.…”
Section: Methodsmentioning
confidence: 99%
“…Content analysis has been extensively used in examining SED practices (Kamal and Deegan, 2013; Novelini and Fregonesi, 2013; Pesci and Costa, 2014; Rahma and Anis, 2013; Talebnia et al , 2013; Van de Burgwal and Vieira, 2014). Content analysis refers to the process of making inferences based on objective coding of information.…”
Section: Methodsmentioning
confidence: 99%
“…One of the reasons both businesses and academics in developing countries are not dealing with CSR commitments might be poor commercial and economic infrastructures. In Iran, for instance, social responsibility and reporting are in the infancy; specifically, after reviewing the Iranian company websites, Farivar and Scott-Ladd (2016) indicated that CSR disclosure is still in its early stages; however, during the recent years, due to the factors, such as Iranian Government pressure on businesses, privatization and relative competitive environment, the awareness of heavy-pollution industries toward employees working conditions, environmental protection, consumer needs and stakeholders' interests has increased (Talebnia et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Aktivitas Corporate Social Responsibility (CSR) menunjuk pada berbagai kegiatan sosial yang melampaui batas lingkungan perusahaan (Kitzmueller & Shimshack, 2012). Perusahaan mengungkapkan Corporate Social Responsibility (CSR) dengan mempromosikan berbagai hal sosial yang diminati oleh masyarakat yang dapat membangun dan meningkatkan hubungan antara perusahaan dengan masyarakat maupun pihak lain (Hossain et al, 2013). Perusahaan bekerja sama dengan masyarakat dan lingkungan, karena dari lingkungan sekitar perusahaan mendapatkan pelanggan, pemasok, pekerja, investor, dan stakeholders yang secara langsung maupun tidak langsung berpengaruh terhadap keberadaan perusahaan itu sendiri (Bhuiyan et al, 2015).…”
Section: Pendahuluanunclassified